Study on the mechanism of institutional capacity impact of public administrative service providers on the investment and business environment of the province - Le Van Hoa; Diu Duc Ha; Nguyen Quynh Huy (Journal of State Management, 2025)
A province's investment and business environment is a crucial factor in the development of enterprises and the local socio-economic landscape. This environment, however, is influenced by multiple factors, including the institutional capacity of public administrative service providers related to investment and business, which is a key determinant. Therefore, improving the investment and business environment requires a strong focus on enhancing the institutional capacity of these agencies. This study, through a comprehensive analysis and synthesis of existing research, clarifies the mechanism through which institutional capacity impacts the investment and business environment of the province.